Asteroseismology and spectropolarimetry: opening new windows on the internal dynamics of massive stars. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Mathis, S.; Neiner, C.
Abstract: In this article, we show how asteroseismology and spectropolarimetry allow to probe dynamical processes in massive star interiors. First, we give a summary of the state-of-the-art. Second, we recall the MHD mechanisms that take place in massive stars. Next, we show how asteroseismology gives strong constraints on the internal mixing and transport of angular momentum while spectropolarimetry allows to unravel the role played by magnetic fields.